CORRUPTION PREVENTION AND MANAGEMENT TAKEN BY REGIONAL HEAD IN ISLAMIC CRIMINAL LAW PERSPECTIVE - Misnan Misnan; Nelvita Purba; Mustamam Mustamam (Jurnal Ilmiah METADATA, 2021)
Studies of corruption in the perspective of religion are still very limited. Whereas in the Islamic legal treasury there are various references to the problem of corruption that can be used as references or material for reflection that can be used as a basis in conducting policies to combat corruption. In the Qur'an and Sunnah there are so many relevant propositions regarding corruption, which can be used as the main source of law in formulating criminal acts of corruption and their mitigation efforts. The problem in this study, namely regarding how the qualifications of acts of corruption in the perspective of Islamic criminal law? What is the criminal sanction for each qualification of acts in a criminal act of corruption according to Islamic criminal law? What are the efforts and obstacles in preventing and overcoming corruption by the regions in the perspective of Islamic criminal law ?. The type of this research is normative juridical research. The data analysis used in this study is qualitative data analysis. Based on the results of the study, corruption in the perspective of Islamic law is qualified as jarimah ta’zir. In jinayah fiqh, several acts that are identical with corruption are identified in 4 (four) types, namely ghulu, risywah, betrayal and ghasab. Corruption is a criminal offense that is classified in jarimah ta'zir, so the forms, sanctions or penalties to be applied, and the execution of the punishment are left entirely to the government or the authorities. The government is given the freedom to determine the forms of their fingerprints and sanctions according to the benefit to be achieved. Efforts to prevent and eradicate corruption in the perspective of Islamic criminal law are carried out with three strategies, namely: prevention, deductive and refressive strategies.